Tinjauan Yuridis Alih Fungsi Lahan Pertanian Menjadi Perumahan Berdasarkan Peraturan Daerah Kota Bekasi Nomor 3 Tahun 2025 Tentang Perizinan Pemanfaatan Ruang - Irah Nur Khasanah; Julius Caesar Transon Simorangkir (Kampus Akademik Publiser, 2026)
Growing population numbers and rising demand for housing in Bekasi City have given rise to a recurring spatial-planning issue: agricultural land being converted for residential use. Legal instruments are therefore needed to keep space utilization aligned with the spatial plan without sacrificing the protection owed to farmland. This article sets out to examine how such conversion is governed under Bekasi City Regional Regulation Number 3 of 2025 on Space Utilization Licensing, and to assess how that regulation actually operates on the ground. An empirical-normative juridical method was applied, drawing together a statutory, a conceptual, and an empirical approach. Legal materials were gathered through documentary and library-based research covering statutes, regulations, books, journal articles, and official records connected to spatial management in Bekasi City; these materials were then examined qualitatively and descriptively by weighing the written rules against how they are applied in practice. Findings indicate that farmland conversion into housing falls under four licensing instruments for space utilization: Conformity of Space Utilization Activities (KKPR), Environmental Approval, Building Approval (PBG), and the Certificate of Functional Suitability (SLF). From a juridical standpoint, Regional Regulation Number 3 of 2025 lays out a clear legal foundation for licensing as well as for the supervision and control of spatial use. Its practical effectiveness, however, cannot yet be fully gauged, since the regulation only recently took effect and no officially recorded instance of farmland-to-housing conversion has occurred under it so far. Even so, the continued discovery of unlicensed building and space-use violations suggests that oversight and preventive measures still require strengthening, so that spatial use throughout Bekasi City remains consistent with both statutory requirements and the spatial plan.